Against Fragmentation: Critical Education Scholarship in a Time of Crisis. Issue 3 (4th May 2019) - Ellison, Scott
Abstract : One of the defining characteristics of critical education scholarship is its focus on critical reflection as a means to inform educational scholarship and pedagogical practice. This article presents findings from a conjunctural analysis of the emergent crisis into which the United States and the global North are entering as a means of critically reflecting on educational scholarship. The analysis demonstrates that the emergent crisis is defined by economic, political, and cultural crises that are connected and animated by the neoliberal political project. The article concludes with a call for critical scholarship and pedagogical practice oriented toward synthetic, recontextualizing analysis.